Multi-Target Approaches in Metabolic Syndrome - Lillich, Felix F.; Imig, John D.; Proschak, Ewgenij (Frontiers in Pharmacology, 2021)
Metabolic syndrome (MetS) is a highly prevalent disease cluster worldwide. It requires polypharmacological treatment of the single conditions including type II diabetes, hypertension, and dyslipidaemia, as well as the associated comorbidities. The complex treatment regimens with various drugs lead to drug-drug interactions and bad patient adherence, resulting in poor management of the disease. Multi-target approaches aim at reducing the polypharmacology and improving the efficacy. This review summarizes the medicinal chemistry efforts to develop multi-target ligands for MetS. Different combinations of pharmacological targets in context of in vivo efficacy and future perspective for multi-target drugs in MetS are discussed.